LIFERAFT OPERATING PROCEDURE AS A SAFETY SUPPORT FOR CREWS ON MV MULYA SENTOSA II - Okvita Wahyuni; Agus Tjahjono (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Pelayaran Malahayati, 2023)
Liferaft is a boat-shaped safety device carried onboard which is equipped with a canopy and survival kits for an emergency situation. This research applied the descriptive method, applied a random sampling technique whose samples were taken from crew of MV Mulya Santosa II. It was aimed to determine (1) causative factors leading to crews' low understanding of liferaft operating procedures on MV Mulya Sentosa II and (2) the impact of crews' low understanding of liferaft operating procedure on MV Mulya Sentosa II, and also (3) to determine any action which could be done to optimize the liferaft utility in MV Mulya Sentosa II in times of emergency (abandoning ship). The research found that there were some factors leading to the crews' low understanding of liferaft operating procedure on MV Mulya Sentosa II, including the lack of emergency drills, the absence of written information about liferaft operating procedure on board, and Deck Officer's low responsibility on performing emergency drills. Some efforts to overcome this situation included implementing emergency drill on board in accordance with the established requirements or guidelines, applying strict sanctions to any Deck Officer who did not implement emergency drills, and having a clear, effective, written information about liferaft operating procedure in place for all the crews to see.